2014
DOI: 10.1111/ene.12613
|View full text |Cite
|
Sign up to set email alerts
|

Substantia nigra neuromelanin magnetic resonance imaging in de novo Parkinson's disease patients

Abstract: Neuromelanin-sensitive MRI techniques can discriminate PD patients from healthy individuals with high sensitivity and specificity. Our findings are consistent with recent findings showing that PD neuromelanin changes remain stable during the course of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
82
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 18 publications
12
82
1
2
Order By: Relevance
“…These observations are in agreement with previous studies and confirmed that NM imaging is sensitive and specific for detecting nigrostriatal damage in PD. 9,10,17,24 The combination of volume and signal loss slightly increased the diagnostic accuracy. 10 In our study, we found a significant increase in diffusivity and a decrease in FA in the 3T NM ROI in patients with PD, which is congruent with previous studies reporting FA reduction 2-4 and increases in RD 2 and MD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These observations are in agreement with previous studies and confirmed that NM imaging is sensitive and specific for detecting nigrostriatal damage in PD. 9,10,17,24 The combination of volume and signal loss slightly increased the diagnostic accuracy. 10 In our study, we found a significant increase in diffusivity and a decrease in FA in the 3T NM ROI in patients with PD, which is congruent with previous studies reporting FA reduction 2-4 and increases in RD 2 and MD.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,17,24 The combination of volume and signal loss slightly increased the diagnostic accuracy. 10 In our study, we found a significant increase in diffusivity and a decrease in FA in the 3T NM ROI in patients with PD, which is congruent with previous studies reporting FA reduction 2-4 and increases in RD 2 and MD. 5 These changes may be explained by cell lossand microstructural damage-induced changes in cell morphology and density and the destruction of diffusion barriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…83 Recent studies have suggested that neuromelanin decrease (whose paramagnetic properties result in high signal on specific T1-weighted magnetic resonance imaging [MRI]) in the SN and locus coeruleus of PD patients may differentiate between PD patients and healthy controls with high sensitivity and specificity. 84 For a research purpose, imaging studies may further contribute in the delineation of different PD phenotypes at diagnosis. A recent fMRI study demonstrated that the subtype-specific functional networks could discriminate among PD patients with TD and non-TD phenotypes and healthy controls.…”
Section: Imaging Biomarkersmentioning
confidence: 99%